PROSEDUR PEMUNGUTAN PAJAK PERTAMBAHAN NILAI (PPN) ATAS JASA PENGIRIMAN PAKET PADA PT POS INDONESIA (PERSERO) MAKASSAR 90000 - Siswati Rachman (Universitas Muhammadiyah Makassar, 2020)
This study aims to determine the procedure for collecting value added tax (VAT) for package delivery services at PT POS INDONESIA (PERSERO) Makassar 90000. The type of research used is qualitative description, which explained between facts and data or information that has been obtained from the place of research.This research was conducted for two months from May 2019 to June 2019, at PT POS INDOENESIA (PERSERO) Makassar 90000. Techniques for collecting data using observation and interviews. The results of the research concluded that the procedure for collecting Value Added Tax (PPN), they are: 1) VAT collection starts when customers submit taxable goods (BKP) in the retail and corporate services section as VAT collectors, 2) Service section provides letter of receipt of receipt to the customer, 3) the service section prints the backsheet as proof of VAT collection then recorded by the accounting department, 4) After being accounted for by the accounting, backsheet and VAT payments deposited to the finance department and then deposited to the state treasury.